Psychological Expected Utility Theory and Anticipatory Feelings - Caplin, A.; Leahy, J. (Quarterly Journal of Economics, 2001)
We extend expected utility theory to situations in which agents experience feelings of anticipation prior to the resolution of uncertainty. We show how these anticipatory feelings may result in time inconsistency. We provide an example from portfolio theory to illustrate the potential impact of anticipation on asset prices.